On Covert Communication Against Sequential Change-Point Detection - Huang, Ke-Wen; Wang, Hui-Ming; Poor, H. Vincent (IEEE transactions on information theory, 2021)
We investigate covert communication under a sequential change-point detection (SCPD) framework, where a transmitter, Alice, attempts to communicate reliably with a receiver, Bob, over an additive white Gaussian noise channel, while simultaneously ensuring covertness (low probability of detection) with respect to an adversary, Willie. Different from the binary hypothesis test based detection framework considered in prior works where Willie collects all signal samples together and makes a decision in a batch manner, we view Willie's detection process as an SCPD process that works in a real-time manner. We establish a new criterion to evaluate the covertness of the communication between Alice and Bob, and investigate the performance of covert communication accordingly. Subject to the proposed constraint on covertness, we investigate the feasible transmit power and transmission duration under three SCPD algorithms, namely, the Shewhart test, the finite moving average chart (FMAC), and the cumulative sum (CUSUM) test, and characterize how the covert communication throughput scales with the average run length to false alarm (ARL2FA) of Willie's detector as the ARL2FA increases without bound. Our theoretical results can be viewed as upper bounds on the covert communication throughput that can be achieved, and we show that compared with the case where Willie performs the CUSUM test, Alice and Bob achieve a higher covert communication throughput if Willie performs the Shewhart test or the FMAC.